2010
DOI: 10.1007/s10555-010-9247-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and breast cancer: implications for immunopathogenesis

Abstract: Current understanding of the role of several cancer risk factors is more comprehensive, as reported for a number of sites, including the brain, colon, breasts, and ovaries. Despite such advances, the incidence of breast cancer continues to increase worldwide. Signals from the microenviroment have a profound influence on the maintenance or progression cancers. Although T cells present the most important immunological response in tumor growth in the early stages of cancer, they become suppressive CD4(+) and CD8(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 95 publications
4
82
0
Order By: Relevance
“…Although the incidence of breast cancer has increased constantly in developed countries over the past few decades, the mortality caused by breast cancer has decreased in recent years, partly because of improved diagnostic and therapeutic techniques and also better understanding of the pathogenesis of the disease [2]. The prognosis of the disease is strongly associated with tumor stage [3] and could also be predicted by biological characteristics of tumor cells, including expression of hormone receptors (HR) and human epidermal growth factor receptor 2 (HER2) [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the incidence of breast cancer has increased constantly in developed countries over the past few decades, the mortality caused by breast cancer has decreased in recent years, partly because of improved diagnostic and therapeutic techniques and also better understanding of the pathogenesis of the disease [2]. The prognosis of the disease is strongly associated with tumor stage [3] and could also be predicted by biological characteristics of tumor cells, including expression of hormone receptors (HR) and human epidermal growth factor receptor 2 (HER2) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their ability to mediate suppression of cancer's immune response is increasingly recognized [9,10] and studies have found that Tregs play important roles in tumor scape [11]. Elevated proportion of Tregs is present within tumors, lymph nodes and peripheral blood of various types of solid and hematologic cancers including breast cancer [12,13]. Besides, frequency of CD4 ?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer becomes one of the most wide-spreading diseases nowadays (Atoum et al, 2010), breast cancer is the most common female malignancy worldwide, and the second leading cause of cancer mortality among women (Downs-Holmes and Silverman, 2011) accounting for 23% of all cancers (Liang et al, 2008) with more than one million new patients are diagnosed annually (Watanabe et al, 2010). Globally it accounts for 18% of all female cancers (Cantu De Leon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%